Effect of laser remelting on microstructure and properties of two Ni-base coatings by supersonic particles deposition. (21st October 2020) - Bingyuan, Han; Shaoyi, Bei; Kebing, Zhou; Yuxiang, Liu; Yan, Zhang; Xue, Yan; Weixing, Hang; Fangfang, Cui; Wenwen, Xu; Wei, Du; Sheng, Zhu
Abstract: Remelting treatment of In718 and In625 coatings deposited by supersonic particles were conducted by using laser technology. The microstructure, phase composition, microhardness, wear resistance and corrosion of the coating before and after remelting were studied. The results showed that defects such as voids and cracks of the deposited coating were eliminated by laser remelting treatment, the microstructure of the coating became compact and uniform and the bonding mode changed from mechanical bonding to metallurgical bonding. The deposited coating consisted of γ -Ni solid solution and Fe3 Ni2 intermetallic compound phase, remelting to form a new phase Ni3 (Al, Ti) and high hard phase carbide (Nb, Mo) C. The average microhardness of the remelted coating was 6.96 GPa, which was 1.72 times than that of the deposited coating. The wear resistance of remelting coating was significantly better than that of deposited coating and substrate, and its wear form was mainly abrasive wear. The corrosion resistance of the coating was significantly improved after remelting treatment.